The Contribution of Post-Conflict Education to Social Transformation and Sustainable Development - Aswin Ariyanto Azis (Global South Review, 2015)
The role of education in post conflict reconstruction has become increasingly important and gained much greater acknowledgment in development studies in recent years. Education is increasingly accepted as an integral part of humanitarian response in emergencies. It can help conflict-affected community and individual to return to normalcy, safeguard the most vulnerable, provide psychosocial care, promote tolerance, unify divided communities, and begin the process of reconstruction and peace building. However, research also suggests that education can encourage intolerance, create or generate inequality, and intensify social tensions that can lead to civil conflict and violence. Education is a key determinant of income, influence, and power. Inequalities in educational access can lead to other inequalities–in income, employment, nutrition and health as well as political position, which can be an important source of conflict. Hence, education has potential to either aggravate the conditions that lead to conflict or to heal them. Nonetheless, the unavoidable conclusions must be that ignoring education, or postponing it, is not an option. This essay attempts to answer question on how post-conflict education be able to contribute to social transformation and sustainable development. It argues that education in general has a key role in both preventing conflict and rebuilding fractured post-conflict societies. Hence it puts forward education as a human development activity and must be undertaken with a development perspective if it is to contribute reversing the damage and to building resilience to prevent further violence conflict.